ANALISIS PERENCANAAN STRUKTUR ATAS PEMBANGUNAN KANTOR PESANTREN MUHAMMADIYAH LIMA KAUM - Masril, Masril; Indah Wahyuni, Elvina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
MTSN Muhammadiyah Lima Kaum which will become the Muhammadiyah Lima Kaum Islamic Boarding School. With the increasing number of students who will study at the pesantren, facilities are needed in the form of an office with an office structure. (SRPMK) because the planning location is in a high earthquake risk location. The planning for this mosque is in accordance with SNI 03-2847-2019 concerning concrete structures, and SNI 03-1726-2019 for planning earthquake- friendly buildings and non-buildings. The method that the author uses for this research is quantitative to obtain the necessary data and qualitative to obtain more extensive information about this research. After the data was complete, the authors began planning the office of the Muhammadiyah Lima Kaum Islamic Boarding School. From the results of the structural analysis, the structural reinforcement is obtained based on the author's analysis. The results obtained for the material used are steel fy 420 MPa and quality fc' 20.75 MPa. For slab reinforcement, reinforcement is used for the x direction Ø10-100 and the y direction Ø10-200. Column design uses steel quality fy 420 MPa and concrete quality fc' 20.75 with a column size of 50cm x 50cm. while the design of beams uses steel quality fy 420 MPa and concrete quality fc' 20.75 with beam size 1 30cm x 50cm and beam 2 25cm x 45cm.. Keywords: Dormitory, Boarding School, Structure, Building, Method